“How Much Does My Implant Weigh?”: Addressing Patient Concern about Weight Gain after Total Hip Arthroplasty - LeRoy, Taryn; Bono, Olivia J.; Bono, James V. (The Journal of Hip Surgery, 2019)
A common concern for patients undergoing joint replacement is that the implant will increase their body weight. In an effort to determine if in fact the joint implant is heavier than the bone removed during surgery, the authors conducted a 3-year review from 11/2014 to 11/2017 of 339 patients who underwent total hip arthroplasty (THA) procedures performed by a single surgeon. In the 339 patients, the bone and tissue removed from the patient was weighed. Using the known weights of each component (cup, head, and stem), the authors calculated the total mass of the hip prosthetic implant. Using deidentified patient data, they reviewed only the weight of bone and tissue removed and the calculated weight of the implant placed in each THA performed by the single surgeon. They subtracted the mass of the bone and tissue removed during surgery from the total mass of the hip implant to determine the net weight differential in the patient following surgery and calculated an average net weight gain of 124.84 g in the 339 patients who underwent THA. This weight gain of 124.84 g is equivalent to 0.275 lbs. Previous studies have only looked at weight gain or loss following total joint replacement with respect to natural weight loss/gain that may be associated with improved mobility following surgery. This is the first study to measure the actual quantifiable net weight differential due to the joint replacement itself. The authors concluded that no appreciable weight gain following THA can be attributed to the weight of the implant.
Keywords: weight gain; implant; total hip arthroplasty